(untitled) (Journal of Patan Academy of Health Sciences, 2018)
A 24 years lady was scheduled for tonsillectomy for recurrent tonsillitis had anaphylaxis and asystole before extubation, she was revived successfully.She had no known history of allergy and exposure to anesthetic agents and was classified as an American Society of Anesthesiologists, ASA I. In the operating theatre, her baseline vitals were unremarkable and remained hemodynamically stable on receiving antibiotic and anesthetic drugs. The anesthetic course remained uneventful throughout the surgery. Upon removal of surgical drapes, upper eyelid swelling was noted, that rapidly progressed to facial area within minutes, and she developed cardiac arrest which was managed with standard protocol and resuscitated successfully.